L' express de Bénarès à la recherche d'Henry J.-M. Levet : récit - Vitoux, Frédéric 1944- (Fayard, 2018)
"After returning from a trip to India in 1898, the poet Henry J.-M. Levet told his friends in Montmartre that he was finishing a novel entitled L'Express de Bénarès, whose characters or episodes he mentioned before them. more funny - but no one ever knew about it. Did Levet really write it? We'll never know. When he died in 1906, at the age of thirty-two, after a few years as vice-consul in Manila and Las Palmas, his parents destroyed his letters and manuscripts. Why did Levet, whom I discovered at the age of seventeen, keep me so permanently obsessed? Why this young man, who has been cherished for more than a century by a few hundred readers, from one generation to the next, as if to perpetuate the circle of the lost poet, and which no one would have known without the perseverance of Fargue, his intimate friend and of Larbaud, who after his death undertook to collect and publish his poems, does he belong to my imagination - or better, to my life? Montbrison, together rare testimonies, dive into the exuberant bohemian Montmartre at the turn of the XIX th and XX thFor centuries, to question me about the contrasting personality of this lonely, ungrateful poet, who brightened his friends with his extravagant outfits, was that not a way of getting to know me better? We always come back to it.»--Translation of page 4 of cover by Fayard
Keywords: Levet, Henry Jean-Marie -- 1874-1906; Geschichte 1874-1906; Schriftsteller; Frankreich; Levet, Henry J.-M. / (Jean-Marie) / 1874-1906; Authors, French / 19th century / Biography; Authors, French / 20th century / Biography; Biografie